EFEKTIFITAS PENGAJIAN RUTIN DALAM MENINGKATKAN PERILAKU BERAGAMA MASYARAKAT - Suriati, Suriati (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi, 2015)
Having a religion is one of the human natural tendencies. This natural tendency will grow and develop when this is fostered continously irrespective of time, age, race, sex and gender roles. Da'wah is regarded as an instrument to call people and foster them continously,  particularly  Muslim community,  in order to develop such a human natural tendency. Since the package of  da'wah  is important to attract people,  Majelis Taklim or Islamic study group as society based-organization is an alternative solution to that purpose.  With continous fostering,  society will have religious behaviour and good attitude which represents an ethics to  Allah, people and environment.